Effect of Methanolic Extract of Dandelion Roots on Cancer Cell Lines and AMP-Activated Protein Kinase Pathway - Rehman, Gauhar; Hamayun, Muhammad; Iqbal, Amjad; Khan, Sumera Afzal; Khan, Hamayoon; Shehzad, Adeeb; Khan, Abdul Latif; Hussain, Anwar; Kim, Ho-Youn; Ahmad, Jamshaid; Ahmad, Ayaz; Ali, Abid; et al. (Frontiers in Pharmacology, 2017)
Ethnomedicinal knowledge of plant-derived bioactives can help us in discovering new therapeutic compounds with great potential. Certainly, dandelion has been used in traditional ethno-medicinal systems (i.e., Chinese, Arabian, Indian and Native American) since long to treat different types of cancer. Though, dandelion is highly vigorous, yet the potential mode of action is still unknown. In the current study, we have investigated the antiproliferative activity of methanolic extracts of dandelion root (MEDr) on cell viability of liver cancer cells (HepG2), breast cancer cells (MCF7), and colon cancer cells (HCT116). We have observed that MEDr (500 µg/ml) drastically decreased (80%) the growth of HepG2 cell line, while the effect on MCF7 and HCT116 cell lines were less pronounced. The MEDr also enhanced the phosphorylation level of AMP-activated protein kinase (AMPK) of HepG2 cells, which is considered crucial in cancer treatment and other metabolic diseases. The AMPK activation by MEDr noticed in the current study was never reported previously. The results regarding the number of apoptotic cells (HepG2 cells) were in line with the cell viability test. The current observations clearly demonstrated the potency of MEDr against liver cancer and validated that dandelion can control AMPK and thus cancer in the treated cell lines.